(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
The writing of school histories is a neglected sub-discipline in the study of heritage. It is, however, imperative that this aspect of the broad tapestry of our local and national heritage is analysed and preserved. As a microcosm of the community which it serves, a school reflects and engages with the greater political, social and economic issues and dynamics at any particular stage in its development. Often relegated to a purely celebratory document marking a centenary, half or quarter century, the account could be purely anecdotal or touch only on those aspects of the school which have contributed to school traditions, neglecting the broader framework within which it functions and with which it engages. It is critical that this aspect of heritage is preserved by historians who take the effort to research and write about this tiny snippet of our national heritage.